Tata Kelola Digital dalam Mencegah Deforestasi dan Memperkuat Ketahanan Pangan di Indonesia: Studi Komparatif Lintas Negara - Muhammad Darwisy Sangaji (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2025)
Deforestation and inefficient land management threaten food security in Indonesia, necessitating a digital governance framework capable of strengthening inter institutional coordination and data transparency. Responding to this urgency, this study adopted a systematic literature review of publications from 2014 to 2023 across six major databases, national policy documents, and international organization reports. From approximately 150 initial results, 45 publications were selected through the screening of titles, abstracts, and full texts. Text screening was then analyzed thematically based on the six dimensions of the OECD digital governance framework. Findings show that implementing digital governance can improve decision making effectiveness, data transparency, and cross-agency coordination in land and food management. International practices in China (real-time centralized data systems), Brazil (satellite monitoring), and the European Union (satellite programs and data transparency) provide essential lessons. However, from a digital government perspective, in terms of maturity, Indonesia is still at an intermediate stage towards the interactive stage. This condition reflects the persistence of fundamental challenges in implementing digital governance, such as low data interoperability, inadequate information disclosure regulations, and limited institutional capacity to implement a digitally integrated government system. To prevent deforestation and strengthen sustainable food security, Indonesia needs to improve data disclosure regulations, develop interoperability platforms across institutions, and increase institutional capacity to implement digital governance principles.